De-anonymiation method for networks based on DeepLink - Pei WANG; Yan JIA; Aiping LI; Qianyue JIANG (网络与信息安全学报)
Existing de-anonymization technologies are mainly based on the network structure.To learn and express network structure is the key step of de-anonymization.The purpose of the user identity linkage is to detect the same user from different social networking platforms.DeepLink is a cross-social network user alignment technology.It learns the structural of the social networks and align anchor nodes through deep neural networks.DeepLink was used to identify de-anonymization social networks,and the results outperforms the traditional methods.